2013
DOI: 10.1021/es401997d
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Controlled Changes in Cadmium Solubility and Solid-Phase Speciation in a Paddy Soil As Affected by Reducible Sulfate and Copper

Abstract: The solubility of Cd in contaminated paddy soils controls Cd uptake by rice, which is an important food safety issue. We investigated the solution and solid-phase dynamics of Cd in a paddy soil spiked with ∼20 mg kg(-1) Cd during 40 days of soil reduction followed by 28 days of soil reoxidation as a function of the amounts of sulfate available for microbial reduction and of Cu that competes with Cd for precipitation with biogenic sulfide. At an excess of sulfate over (Cd + Cu), dissolved Cd decreased during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(118 citation statements)
references
References 60 publications
(135 reference statements)
9
108
1
Order By: Relevance
“…Levels of Mn 2+ used in testing repression may not have been representative of reduced paddy soils. Further study of the interaction of Mn 2+ with Cd 2+ uptake by rice showed that soil solution levels of Mn 2+ in flooded soils strongly inhibited Cd uptake [55] extending the findings of Fulda et al [37] and Sasaki et al [54]. Further, in contrast with Cd absorption by other plant species, increased Zn 2+ had little effect on Cd absorption by NRAMP5.…”
Section: +supporting
confidence: 72%
See 3 more Smart Citations
“…Levels of Mn 2+ used in testing repression may not have been representative of reduced paddy soils. Further study of the interaction of Mn 2+ with Cd 2+ uptake by rice showed that soil solution levels of Mn 2+ in flooded soils strongly inhibited Cd uptake [55] extending the findings of Fulda et al [37] and Sasaki et al [54]. Further, in contrast with Cd absorption by other plant species, increased Zn 2+ had little effect on Cd absorption by NRAMP5.…”
Section: +supporting
confidence: 72%
“…Zn is either strongly adsorbed to soil sorbents or transformed to insoluble ZnS and Cd can precipitate as CdS [28,34], although it has been difficult to document the extent of CdS formation in flooded rice soils even using Extended XRay Absorption Fine Structure (EXAFS) [35][36][37]. Although early researchers who reported the very strong effect of soil reduction on Cd uptake suggested that this could be explained by sulfide formation in flooded soils and formation of CdS [28], EXAFS evidence of CdS was first reported by Khaokew et al [35] with highly contaminated Thai rice soils.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also reported that the spatial organization of S-cycling is more complicated than originally predicted, with SRB differentially distributed in microenvironments (Wieringa et al, 2000;Baumgartner et al, 2006;Fike et al, 2009). Lower pH values within the bioreactors also increased the mobility of sorbed (Fulda et al, 2013;Caraballo et al, 2013) and precipitated phases (Acero et al, 2006;Borch et al, 2009;Chirit¸ a and Schlegel, 2012;Burgos et al, 2012), thus contributing to decreased remediation efficiency.…”
Section: Seasonal Variationsmentioning
confidence: 99%